Investigating the impact of flipped classroom on dual language learners' perceptions and grammatical performance - Shaari, Nurliana Dalila; Shaari, Azianura Hani; Abdullah, Mohammad Ridhuan (Department of English Education, Faculty of Teacher Training and Education, Universitas Syiah Kuala, Banda Aceh, Indonesia, 2021)
Flipped classroom model has received massive attention from many researchers due to its innovative instructional strategy that offers a new perspective to the traditional classroom. However, not many studies have focused on dual language learners (DLL) who face challenges in grasping second language skills and knowledge, due to the multiple linguistic systems that they have to manage. By marrying communicative language teaching (CLT) approach with flipped technique, the present study, therefore, aims to explore dual language learners’ perception towards flipped classroom model in learning English tenses as well as their learning progress using the method. The lessons were conducted using set of culturalised interactive materials. A number of 133 intermediate learners (age 18 to 25) from a vocational college in Malaysia were selected as the research participants and data were collected using one-group pre-test–post-test design, questionnaire and interview. Pre-test and post-test grammar questions were given before and after a six-week intervention program to identify the effectiveness of the materials and instruction. The findings indicated significant differences between the mean scores of the pre-test and post-test. The results also revealed learners’ positive responses and improvement in English grammar through flipped classroom and culturalised interactive materials. This research has suggested some significant impacts of flipped classroom practices using familiar objects and culturalised learning materials. Apart from acknowledging the advantages of flipped classroom model in learning English grammar, the present study also proposes some additional strategies to achieve an effective flipped classroom lesson for dual language learners in Malaysia.